Creating a framework for the prioritization of biosecurity risks to the New Zealand dairy industry. Issue 4 (25th March 2018) - Muellner, P.; Hodges, D.; Ahlstrom, C.; Newman, M.; Davidson, R.; Pfeiffer, D.; Marshall, J.; Morley, C.
Summary: The New Zealand dairy sector relies on robust biosecurity measures to control and mitigate a wide range of threats to the industry. To optimize the prioritization of organisms and manage the risk they pose to the sector in a transparent and credible way, the Dairy Biosecurity Risk Evaluation Framework (D‐BRiEF) was developed. This comprehensive framework was specifically designed for decision support, using a standardized approach to address the full spectrum of biosecurity threats to the sector, including exotic and endemic animal disease organisms, pest plants and insects. D‐BRiEF is underpinned by three main processes, namely (i) hazard identification; (ii) multicriteria risk assessment; and (iii) communication for risk management. Expert knowledge and empirical data, including associated uncertainty, are harnessed in a standardized format. Results feed into a probability‐impact model that was developed in close collaboration with dairy sector economists to provide overall comparative 10‐year quantitative economic impact estimates for each assessed risk organism. A description of the overarching framework, which applies to diverse organism groups, is presented with detailed methodology on both endemic and exotic animal disease risk organisms. Examples of visual outputs are included, although actual ranking results are not reported due to industry confidentiality. D‐BRiEF can provide a decision advantage to DairyNZ biosecurity risk managers and sector stakeholders by creating a transparent process that can be interrogated and updated at multiple levels to fully understand the layers of risk posed by different organisms.